2001
DOI: 10.1074/jbc.m106824200
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Folate Receptor mRNA-binding trans-Factor from Human Placenta

Abstract: The interaction of an 18-base cis-element in the 5-untranslated region of human folate receptor (FR)-␣ mRNA with a cytosolic trans-factor protein is critical for the translation of FR (Sun, X.-L., and Antony, A. C. (1996) J. Biol. Chem. 271, 25539 -25547). This trans-factor was isolated to apparent homogeneity as a 43-and 38-kDa doublet from human placenta using poly(U)-Sepharose, followed by preparative sodium dodecyl sulfate-polyacrylamide gel electrophoresis and electro-elution as major purification steps. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 34 publications
4
55
1
Order By: Relevance
“…Indeed, Western blots of cytosolic S-100 fractions of HeLa-IU 1 cells using this antiserum (see Fig. 5B) confirmed a major band corresponding to hnRNP-E1 and a minor band corresponding to hnRNP-E2 (and no other contaminant proteins); this pattern was not dissimilar to the doublet found on SDS-PAGE of hnRNP-E1 isolated from human placenta (12) or Western blots of rat brain probed with anti-hnRNP-E1 and -E2 antiserum (31). Because there was no change in the expression of hnRNP-E1 per mg of cytosolic (S-100 fraction) proteins from HeLa-IU 1 -HF and HeLa-IU 1 -LF cells on Western blots (Fig.…”
Section: In Vitro Translation Of [ 35 S]fr In the Presence Of Dl-ormentioning
confidence: 79%
See 2 more Smart Citations
“…Indeed, Western blots of cytosolic S-100 fractions of HeLa-IU 1 cells using this antiserum (see Fig. 5B) confirmed a major band corresponding to hnRNP-E1 and a minor band corresponding to hnRNP-E2 (and no other contaminant proteins); this pattern was not dissimilar to the doublet found on SDS-PAGE of hnRNP-E1 isolated from human placenta (12) or Western blots of rat brain probed with anti-hnRNP-E1 and -E2 antiserum (31). Because there was no change in the expression of hnRNP-E1 per mg of cytosolic (S-100 fraction) proteins from HeLa-IU 1 -HF and HeLa-IU 1 -LF cells on Western blots (Fig.…”
Section: In Vitro Translation Of [ 35 S]fr In the Presence Of Dl-ormentioning
confidence: 79%
“…Similar methods were also employed to evaluate the biosynthesis of hnRNP-E1 using antihnRNP-E1 antiserum (12) substituted for anti-FR antiserum (24) (24). Our anti-hnRNP-E1 peptide antiserum (12) developed against the hnRNP-E1 peptide sequence SLAQYLINARLSSEKGMGC contained shared sequences (underlined) with hnRNP-E2 (a closely related protein with 83% homology in its total amino acid sequence), predicting that this antiserum would recognize shared epitopes in both proteins, which are expressed in these HeLa cells (30). Indeed, Western blots of cytosolic S-100 fractions of HeLa-IU 1 cells using this antiserum (see Fig.…”
Section: In Vitro Translation Of [ 35 S]fr In the Presence Of Dl-ormentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) This domain binds other members of the hnRNP family, including hFip1, CstF-64, hnRNP C1/C2, and polypyrimidine tract-binding protein (13). (iii) Earlier, we purified hnRNP-E1 using poly(U)-Sepharose affinity chromatography (9), suggesting that hnRNP-E1 would bind the HPV16 57-nucleotide poly(U)-rich cis-element. Subsequent studies on the binding of purified recombinant GSThnRNP-E1 to HPV16 57-nucleotide poly(U)-rich cis-element in the presence of physiological concentrations of L-homocysteine, as well as mutation studies involving this cis-element, indicated the specificity and importance of this interaction (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier we had determined that up-regulation of folate receptors in cervical cancer cells during folate deficiency involves the binding of hnRNP-E1 to an 18-base cis-element in the 5Ј-untranslated region of folate receptor-␣ mRNA, which triggers an increase in folate receptor biosynthesis at the translational level (8,9). Because this RNA-protein interaction was stimulated by homocysteine, which accumulates intracellularly during folate deficiency, this work established a link between perturbed folate metabolism and coordinated translational regulation of folate receptors (10).…”
mentioning
confidence: 99%